Urinary CXCL10: a marker of nephritis in lupus patients - M. A. Marie; R. E. Abu Khalil; H. M. Habib (PAGEPress Publications, 2014)
Systemic lupus erythematosus (SLE) is a connective tissue disease characterized by the formation of autoantibodies and immune complexes. Lupus nephritis is one of the hallmark features of SLE. CXCL10 is a chemokine secreted by IFNg- stimulated endothelial cells and has been shown to be involved in the pathological processes of autoimmune diseases. The objective was to measure urinary CXCL10 in SLE patients, to compare levels between nephritis and non-nephritis groups and to study its correlation with other variables. Sixty lupus patients were enrolled in our trial. Thirty patients had lupus nephritis and the other 30 were without evidence of lupus nephritis. Thirty healthy subjects were willing to participate as a healthy control group. Renal biopsy was performed for lupus nephritis group. Urinary CXCL10 was measured using the ELISA technique. Serum creatinine, C3, C4 and 24 h urinary proteins were measured. Lupus activity was assessed using systemic lupus erythematosus disease activity index (SLEDAI) scoring system. Renal activity was measured using renal activity scoring system. CXCL10 was significantly higher in lupus nephritis patients than in lupus patients without nephritis. CXCL10 was significantly correlated with renal activity score, 24 hours urinary proteins and the SLEDAI score. It is highly valid predictor of SLE nephritis with high sensitivity and specificity. CXCL 10 a highly sensitive and specific non-invasive diagnostic tool for lupus nephritis patients.